Efeito das funções executivas no desempenho cognitivo de idosos com envelhecimento normal e patológico - Rafaela Teixeira de Ávila (2014)
Executive functions correspond to a set of cognitive processes that when integrated permit the subject to intentionally drive behavior to goals. Are always required when plans are formulated and when is acquiring new knowledge. They are necessary to manage human behavior and to guarantee success in everyday life functions. The process of healthy aging is marked by a decline in executive functions, being this decline pronounced in Mild Cognitive Impairment (MCI) and in Alzheimers disease (AD). The aim of this dissertation was to evaluate the effects of executive functions, even indirectly, on other cognitive processes in elderly with normal aging, with MCI and with AD. We develop two studies conducted through mediation analysis to investigate the mechanisms by which a variable exerts its effect on other. The results of both studies indicated that executive functions influence both directly and indirectly in other cognitive processes, thus suggesting that their level of functioning influences broadly and in diversified ways on cognitive performance. We observed that, especially on pathological aging group, when compared to normal aging, a greater involvement of executive functions is required as a compensatory resource. We concluded that special attention should be directed to the executive functions in the neuropsychological assessment of elderly, since executive deficits may influence the efficiency of other cognitive processes.